1998
DOI: 10.1111/j.1365-2044.1998.53s104.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the predictive performance of a ‘Diprifusor’ TCI system

Abstract: SummaryThe predictive performance of a 'Diprifusor' target controlled infusion system for propofol was examined in 46 patients undergoing major surgery, divided into three age groups (18-40, 41-55 and 56-80 years). Measured arterial propofol concentrations were compared with values calculated (predicted) by the target controlled infusion system. Performance indices (median performance error and median absolute performance error) were similar in the three age groups, with study medians of 16.2% and 24.1%, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
75
1
7

Year Published

2003
2003
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(87 citation statements)
references
References 16 publications
4
75
1
7
Order By: Relevance
“…In the original study by Swinhoe et al [8], blood samples were collected at suitable times to evaluate all phases of a target-controlled infusion of propofol including planned increases and decreases in target setting in patients undergoing major surgery. Thus, use of data from this study has allowed a comprehensive evaluation of the predictive performance of three models in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the original study by Swinhoe et al [8], blood samples were collected at suitable times to evaluate all phases of a target-controlled infusion of propofol including planned increases and decreases in target setting in patients undergoing major surgery. Thus, use of data from this study has allowed a comprehensive evaluation of the predictive performance of three models in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This was a computer simulation study using data collected in the principal clinical study used to evaluate the predictive performance of the Diprifusor TCI system [8]. As a simulation study, this work was not reviewed by an institutional review board, but the original study was approved by the South Sheffield Research Ethics Committee.…”
Section: Methodsmentioning
confidence: 99%
“…The comparable intersubject levels of anesthesia due to the computer-assisted propofol application induces intraoperative SSEP changes that can be reliably predicted. [18][19][20]25 The influence of midazolam used for premedication can be neglected, as several studies showed no or only a transient effect on SSEP latencies. 22,26,27 Also the application of low doses of opioids (fentanyl) is not supposed to induce the predictable changes on SSEP latencies.…”
Section: Discussionmentioning
confidence: 99%
“…This allows longlasting anesthesia and the possibility of comparable anesthesia. 17,19,20 In the present study, the clinical reproducibility and reliability of pre-, intra-and postoperative SSEP recordings were assessed in uneventful scoliosis surgery. Firstly, the impact of anesthesia was calculated in an intersubject comparison of SSEP parameter differences between preoperative and intraoperative SSEP.…”
Section: Introductionmentioning
confidence: 99%
“…Body weight is used as an input parameter for Diprifusor™. Predicted plasma propofol concentration (Cp) and measured plasma propofol concentration (Cm) were found to be correlated, in spite of the slightly greater values of Cm compared to Cp [1][2][3][4]. If Cm is higher than Cp, arousal delay may occur; if Cm is lower than Cp, it may lead to intraoperative body movement and awakening during surgery, which may result in poor prognosis for the patient.…”
Section: Introductionmentioning
confidence: 99%